2020
DOI: 10.1002/chem.202002135
|View full text |Cite
|
Sign up to set email alerts
|

Phenol Oxidation by a Nickel(III)–Fluoride Complex: Exploring the Influence of the Proton Accepting Ligand in PCET Oxidation

Abstract: In order to gain insighti nto the influence of the H +-accepting terminal ligand in high-valent oxidant mediated protonc oupled electron transfer (PCET) reactions, the reactivity of ah ighv alent nickel-fluoride complex [Ni III (F)(L)] (2,L = N,N'-(2,6-dimethylphenyl)-2,6-pyridinecarboxamidate) with substituted phenols was explored. Analysis of kinetic data from these reactions (Evans-Polanyi, Hammett, and Marcus plots, and KIE measurements) and the formed products show that 2 reacted with electron rich phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 70 publications
5
17
0
Order By: Relevance
“…109−111 However, for a neat transfer of hydrogen atom (one-step), dependence on the redox driving force is minimal, and thus, a 0 slope is expected in the plot of (RT/F) ln k 2 versus E ox . Close to 0 slope and a relatively large KIE, on the one hand, have been reported for the phenolic O−H bond abstraction reactions of the cumylperoxyl radical (slope = −0.05) 112 and [Mn IV (ttppc)(OH)] (−0.12), 113 [Fe IV (ttppc)-(OH)] (−0.19, KIE = 2.9), 113 Ni III (Cl) (−0.12, KIE = 2.4), 48 and Ni III (F) complexes (−0.11, KIE = 18), 114 whereby a HAT reaction mechanism is implicated. On the other hand, Itoh and co-workers observed a slope of −0.72 (and KIE = 1.21−1.56) for the reaction of the (μ-η 2 :η 2 -peroxo)dicopper(II) complex and phenol derivatives, and an endergonic ET coupled with PT mechanism was documented.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…109−111 However, for a neat transfer of hydrogen atom (one-step), dependence on the redox driving force is minimal, and thus, a 0 slope is expected in the plot of (RT/F) ln k 2 versus E ox . Close to 0 slope and a relatively large KIE, on the one hand, have been reported for the phenolic O−H bond abstraction reactions of the cumylperoxyl radical (slope = −0.05) 112 and [Mn IV (ttppc)(OH)] (−0.12), 113 [Fe IV (ttppc)-(OH)] (−0.19, KIE = 2.9), 113 Ni III (Cl) (−0.12, KIE = 2.4), 48 and Ni III (F) complexes (−0.11, KIE = 18), 114 whereby a HAT reaction mechanism is implicated. On the other hand, Itoh and co-workers observed a slope of −0.72 (and KIE = 1.21−1.56) for the reaction of the (μ-η 2 :η 2 -peroxo)dicopper(II) complex and phenol derivatives, and an endergonic ET coupled with PT mechanism was documented.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…This complex reacts with Ph 3 C· to give Ph 3 CN 3 (90%), indicating it is capable of efficient N 3 · to carbon radicals. Although it is known that certain Fe III complexes can carry out C–H activation without an external oxidant, we found that 7 shows only minor thermal decomposition in the presence of excess Ph 3 CH at 50 °C, and there is no trace of the azidation product Ph 3 CN 3 .…”
Section: Resultsmentioning
confidence: 56%
“…A similar type of V-shaped plot was reported for the OAT and HAT reactions of Mn V (O)­(TBP 8 Cz) [TBP 8 Cz = octakis­( p - tert -butylphenyl)­corrolazinato 3– ], and the HAT reaction of a Mn V (NTs)­(corrole) complex . A recent study showed such a mechanistic switch for the reaction of a nickel­(III) fluoride complex with substituted phenols . We speculate that electron-withdrawing halide groups create a partial positive charge at the phosphorus atom through an inductive effect, which makes the (4-F-C 6 H 4 ) 3 P or (4-Cl-C 6 H 4 ) 3 P substrate electrophilic in nature, and reversal of the OAT reaction occurs with these substrates .…”
Section: Resultsmentioning
confidence: 97%
“…70 A recent study showed such a mechanistic switch for the reaction of a nickel(III) fluoride complex with substituted phenols. 71 We speculate that electron-withdrawing halide groups create a partial positive charge at the phosphorus atom through an inductive effect, which makes the (4-F-C 6 H 4 ) 3 P or (4-Cl-C 6 H 4 ) 3 P substrate electrophilic in nature, and reversal of the OAT reaction occurs with these substrates. 69 Then we examined Hammett analysis of the OAT reaction of 2-Ca 2+ with different (4-X-C 6 H 4 ) 3 P substrates.…”
Section: ■ Results and Discussionmentioning
confidence: 99%